Maternal nanos regulates zygotic gene expression in germline progenitors of Drosophila melanogaster. - Asaoka, M.; Sano, H.; Obara, Y.; Kobayashi, S. (Mechanisms of Development, 1998)
Maternal Nanos (Nos) protein is required for germline development in Drosophila embryos. Here we show that Nos regulates zygotic gene expression in the germline progenitors, or pole cells. In order to probe the gene expression in pole cells, we screened ten enhancer-trap lines which showed beta-gal expression in pole cells. All of these enhancer-trap markers were fully activated in pole cells after their migration to the embryonic gonads. In the pole cells lacking Nos, the expression of nine out of ten enhancer-trap markers was affected. Among nine markers, five (Type-A) were prematurely expressed in the pole cells during the course of their migration. The expression of other four markers (Type-B) initiated correctly after pole-cell migration, but their expression was significantly reduced. Thus, we conclude that the maternal Nos plays a dual role in zygotic gene regulation in pole cells: to define the stages of expression for Type-A markers, and to enhance expression for Type-B markers. Contrary to our results, "Heller and Steinmann-Zwicky (1998)" have recently reported that no premature expression of Type-A markers occurs in the pole cells of embryos derived from nos mutant females. This discrepancy is due to the difference in the nos mutant alleles used for these analyses. We used the much stronger allele, nosBN.